Measurement of the mechanical loss of prototype GaP/AlGaP crystalline coatings for future gravitational wave detectors. (5th January 2015) - Cumming, A V; Craig, K; Martin, I W; Bassiri, R; Cunningham, L; Fejer, M M; Harris, J S; Haughian, K; Heinert, D; Lantz, B; Lin, A C; Markosyan, A S; et al.
Abstract: Thermal noise associated with the dielectric optical coatings used to form the mirrors of interferometric gravitational wave detectors is expected to be an important limit to the sensitivity of future detectors. Improvements in detector performance are likely to require coating materials of lower mechanical dissipation. Typically, current coatings use multiple alternating layers of ion-beam-sputtered amorphous silica and tantalum pentoxide (doped with titania). We present here measurements of the mechanical dissipation of promising alternative crystalline coatings that use multi-layers of single crystal gallium phosphide (GaP) and aluminium gallium phosphide (AlGaP) that are epitaxially grown and lattice matched to a silicon substrate. Analysis shows that the dissipation of the crystalline coating materials appears to be significantly lower than that of the currently used amorphous coatings, potentially enabling a reduction of coating thermal noise in future gravitational wave detectors.